2020
DOI: 10.3329/cardio.v13i1.50568
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Acute Cardiovascular Diseases in Bangladesh- A Time Tested Medical Emergency to deal with

Abstract: Covid-19 pandemic has affected millions of patients, killed more than half a million, and poses major health threat globally. There is high demand for clinical resources and bed space for COVID- 19 patients. Admission of patient of any cardiac emergency in a common block of hospital, country like Bangladesh, may exposes the risk of infection among non-COVID patient. Patient with COVID- 19 and pre-existing cardiovascular diseases (CVD) have increased risk of further aggravation and death. COVID-19 infection is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…In line with this, it should be mentioned that a previous studies found that the most common demographic factor leading to disease severity is age, followed by being male. [19][20][21] Another study has found that age and comorbidities were contributing factors for increasing mortality or progression of the disease. 17 A study expressed that being senior citizen and having coronary vascular disease were appeared to increase the risk of COVID-19 death.…”
Section: Discussionmentioning
confidence: 99%
“…In line with this, it should be mentioned that a previous studies found that the most common demographic factor leading to disease severity is age, followed by being male. [19][20][21] Another study has found that age and comorbidities were contributing factors for increasing mortality or progression of the disease. 17 A study expressed that being senior citizen and having coronary vascular disease were appeared to increase the risk of COVID-19 death.…”
Section: Discussionmentioning
confidence: 99%